BS ISO 22459. Fine ceramics (advanced ceramics, advanced technical ceramics). Reinforcement of Ceramic composites. Determination of distribution of tensile strength and of tensile strain to failure of filaments within a multifilament tow at ambient temperature. (4th September 2019) - British Standards Institution,
No abstract available